Understanding exposure : how to shoot great photographs with any camera - Peterson, Bryan, 1952- (Amphoto Books, 2010)
Understanding Exposure has demystified the complex concepts of exposure for countless photographers. Now updated with current technologies, more than one hundred new images, and an all-new chapter, this new edition will inspire you more than ever to free yourself from "auto" and create the pictures you truly want. In his trademark easy-to-understand style, author Bryan Peterson explains the relationship between aperture and shutter speed, including how to achieve successful exposures in seemingly difficult situations. You'll learn: Which aperture gives you the greatest contrast and sharpness, and when to use it -- Which apertures guarantee the background remains an out-of-focus tone -- Which one aperture--when combined with the right lens--creates an area of sharpness from three feet to infinity -- How to creatively use shutter speed to either freeze an action or imply motion -- Where to take a meter reading when shooting a sunset, snow, or a city at dusk. With new information on white balance, flash, HDR, and more, this updated classic will inspire you to stop guessing and take control of your settings for better photos anytime, anywhere, and with any camera.